The Phase Transition of Higher Dimensional Charged Black Holes - Xiongying Guo; Huaifan Li; Lichun Zhang; Ren Zhao (Advances in High Energy Physics)
We have studied phase transitions of higher dimensional charge black hole with spherical symmetry. We calculated the local energy and local temperature and find that these state parameters satisfy the first law of thermodynamics. We analyze the critical behavior of black hole thermodynamic system by taking state parameters (Q,Φ) of black hole thermodynamic system, in accordance with considering the state parameters (P,V) of van der Waals system, respectively. We obtain the critical point of black hole thermodynamic system and find that the critical point is independent of the dual independent variables we selected. This result for asymptotically flat space is consistent with that for AdS spacetime and is intrinsic property of black hole thermodynamic system.